PENGARUH DANA DESA, DAK FISIK DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI PROVINSI BENGKULU - barika barika (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2020)
The purpose of this study was to determine how the influence of village funds, Special allocation of physical funds and Economic growth on poverty in Bengkulu province. The data used is panel data which is a combination of 9 regencies in Bengkulu province in 2016-2019. The analysis technique used is multiple panel data regression. The result shows that the village fund variable have negative and significant on poverty. Special allocation of physical funds variable and economic growth variable are not significant in reducing poverty levels in districts in Bengkulu province.